Prereduction traction for the prevention of avascular necrosis before closed reduction for developmental dysplasia of the hip: a meta-analysis - Park KB; Vaidya VN; Shin H; Kwak YH (Dove Medical Press, 2018)
Kun-Bo Park,1 Viranchi Narendra Vaidya,2 Hyejung Shin,3 Yoon Hae Kwak4 1Division of Orthopaedic Surgery, Severance Children’s Hospital, Yonsei University College of Medicine, Seoul, Korea; 2Division of Orthopaedic Surgery, Kpond Children’s Superspeciality Hospital, Aurangabad, India; 3Biostatistics Collaboration Unit, Medical Research Center, Yonsei University College of Medicine, Seoul, Korea; 4Department of Orthopaedic Surgery, Hallym Sacred Heart Hospital, Hallym University College of Medicine, Anyang, Korea Background and purpose: Avascular necrosis (AVN) is one of the common complications after closed reduction and hip spica cast for developmental dysplasia of the hip (DDH). Prereduction traction has been used to reduce a dislocated hip or decrease the risk of AVN, but there are conflicting results in prevention effects on AVN. The purpose of this study was to systematically review the current literature and evaluate the effect of prereduction traction in preventing AVN in children with DDH treated by closed reduction through a meta-analysis. Materials and methods: A systematic review of the literature was performed using PubMed and EMBASE with variations of three major terms: 1) hip dislocation; 2) closed reduction; and 3) avascular necrosis. Seven studies that could compare the incidence of AVN between the traction and no-traction group were included. Methodological quality was assessed, a heterogeneity test was done (p=0.008), and the pooled risk ratios were estimated. Results: The association between traction and AVN was assessed, using data on 683 hips treated by closed reduction. The incidence of AVN in the traction and no-traction groups ranged from 5% to 47.7% and from 0% to 72.7%, respectively. A meta-analysis with a random effects model indicated no significant difference in the incidence of AVN between traction and no-traction groups (p=0.536). Conclusion: There was insufficient evidence to decide the efficacy of prereduction traction before closed reduction in reducing the risk of AVN in patients with DDH in this meta-analysis. To recommend prereduction traction for the prevention of AVN, long-term follow-up studies considering age, severity of dislocation, and appropriate traction method are needed. Keywords: developmental dysplasia of the hip, traction, closed reduction, avascular necrosis